2016
DOI: 10.21037/jtd.2016.02.46
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling change during the early development of silicosis disease

Abstract: Background: Silicosis is one of several severe occupational diseases for which effective diagnostic tools during early development are currently unavailable. In this study we focused on proteomic profiling during the early stages of silicosis to investigate the pathophysiology and identify the proteins involved.Methods: Two-dimensional (2D) gel electrophoresis and MALDI-TOF-MS were used to assess the proteomic differences between healthy individuals (HI), dust-exposed workers without silicosis (DEW) and silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Numerous studies have shown that pulmonary fibrosis is mainly caused by the activation of macrophages, which release inflammatory factors and cytokines to influence the activation and migration of downstream effector cells. 1,4,5,31 However, the direct effects of SiO 2 on protein production and functional changes in pulmonary fibroblasts have not been studied extensively. The current study focused mainly on functional changes in fibroblasts in the fibrosis stage, which suggests that the direct effect of SiO 2 on fibroblasts may play an important role in the pathogenesis of silicosis (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that pulmonary fibrosis is mainly caused by the activation of macrophages, which release inflammatory factors and cytokines to influence the activation and migration of downstream effector cells. 1,4,5,31 However, the direct effects of SiO 2 on protein production and functional changes in pulmonary fibroblasts have not been studied extensively. The current study focused mainly on functional changes in fibroblasts in the fibrosis stage, which suggests that the direct effect of SiO 2 on fibroblasts may play an important role in the pathogenesis of silicosis (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Once diagnosed, it is already in the late stage of irreversible fibrosis, and effective treatment for pulmonary fibrosis in the late stage is lacking. 4 The pathophysiology of silicosis starts with phagocytosis of silica in macrophages, which causes an inflammatory cascade that leads to excessive fibroblast proliferation and migration, and gradually forms fibrosis. 5,6 Despite numerous studies that have been conducted to explore the toxicity of crystalline silica, the specific mechanism underlying silicosis is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cell accumulation, collagen deposition, or malignant mesothelioma in silica- or asbestos-treated mice was markedly decreased by suppressing genetically or pharmacologically these key inflammatory mediators ( 13 , 29 ). Increased levels of TNF-α, IL-1, IFN-γ, and IL-17 have been observed in human under conditions of developing silicosis, asbestosis or mesothelioma ( 30 33 ). These findings convincingly indicate a causal relationship between excessive or maintained accumulation of pro-inflammatory cells and cytokines and the establishment of particle-induced chronic diseases.…”
Section: Inflammation As the Driving Forcementioning
confidence: 99%
“…Several biomarkers, such as interleukin-1β, type IV collagen, tumor necrosis factor-α, neopterin, and proteomic profiling, have shown potential significance in patients with lung fibrosis [ 18 – 21 ]. However, no previous investigations have evaluated the diagnostic values of pneumocyte-derived biomarkers in various pneumoconioses.…”
Section: Introductionmentioning
confidence: 99%